Neuromyelitis Optica Spectrum Disease Presenting in Pregnancy: A Case Report and a Literature Review - Huda Abbas Ali Isa; Fatema Hasan; Zainab Mohd Al Aswad; Naeema Ahmed Abdulkareem (Medical Science: Trends and Innovations Vol. 6, 2025)
Background: Acute transferred Myelitis (ATM) or Neuromyelitis Optica spectrum disorder (NMOSD) is one of the rare autoimmune diseases that occur in the central nervous system (CNS), which mainly targets the spinal cord and the optic nerve, resulting in vision loss and paralysis. Purpose: This case report highlights a rare instance of a 26-week pregnant woman presenting with limb numbness, diagnosed with acute transverse myelitis (ATM) following COVID-19 vaccination. Notably, she tested positive for neuromyelitis optica (NMO) but did not exhibit the typical symptoms of blurred vision. Methods: Data was collected from I Seha in Salmaniya Medical Complex in Bahrain, providing a comprehensive overview of the patient’s clinical journey. Results: The patient was treated with carbamazepine, steroids, and clexane (Low molecular weight heparin - Enoxaparin sodium), leading to the successful delivery of a healthy baby at 34 weeks. However, two years postpartum, she reported new episodes of blurred vision and numbness. Subsequent treatment with Rituximab resulted in significant improvement, with a diagnosis of Devic’s disease established. Conclusion: Acute transverse myelitis is a rare condition, particularly during pregnancy, and in this case, symptoms of Devic’s disease were masked by the absence of blurred vision. This condition predominantly affects females in their 20s during childbearing years and can lead to complications such as premature delivery. Effective management includes steroids and antiepileptic drugs, with clexane playing a crucial role in preventing embolisms. A delivery mode may vary based on obstetric factors, and MRI remains the gold standard for diagnosis. Close follow-up is essential for optimal patient outcomes.